2019
DOI: 10.1016/j.ajog.2018.10.031
|View full text |Cite
|
Sign up to set email alerts
|

A group-based yoga program for urinary incontinence in ambulatory women: feasibility, tolerability, and change in incontinence frequency over 3 months in a single-center randomized trial

Abstract: Structured Abstract Background: Due to the limitations of existing clinical treatments for urinary incontinence, many women with incontinence are interested in complementary strategies for managing their symptoms. Yoga has been recommended as a behavioral self-management strategy for incontinence, but evidence of its feasibility, tolerability, and efficacy is lacking. Objectives: To evaluate the feasibility and tolerability of a group-based therapeutic yoga program for ambulatory middle-aged and older women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 57 publications
(41 reference statements)
2
16
0
3
Order By: Relevance
“…All six included studies described the methods used for random sequence generation and were free from reporting bias. Two out of the six included studies reported the methods used for allocation concealment [33,34]. None of the included studies reported blinding of participants; however, assessors were blinded in three out of the six included studies [33][34][35].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All six included studies described the methods used for random sequence generation and were free from reporting bias. Two out of the six included studies reported the methods used for allocation concealment [33,34]. None of the included studies reported blinding of participants; however, assessors were blinded in three out of the six included studies [33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Two out of the six included studies reported the methods used for allocation concealment [33,34]. None of the included studies reported blinding of participants; however, assessors were blinded in three out of the six included studies [33][34][35]. The completeness of outcome data for each main outcome, including attrition and exclusions from the analysis were adequately described in one study [33].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations